2018
DOI: 10.3892/mmr.2018.8380
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from oxidized LDL-stimulated macrophages attenuate the growth and tube formation of endothelial cells

Abstract: Oxidized low-density lipoprotein (oxLDL) has a critical role in the development of atherosclerosis. The participation of oxLDL‑stimulated macrophages has been well‑established in atherosclerosis, however the underlying mechanisms are unclear. Macrophage‑derived exosomes are actively released and are involved in numerous physiological and pathological processes. However, the function of exosomes secreted by oxLDL‑stimulated macrophages in atherosclerosis remains unknown. Exosomes from oxLDL‑treated macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…For example, EVs from atherogenic macrophages promote plaque formation in atherosclerosis. These EVs restrained the migration of naïve macrophage out of plaques and reduced the growth and tube formation of endothelial cells (ECs), increasing plague progression 69 , 70 . Moreover, excessive lipoproteins accumulation induces the release of Mφ-EVs enriched with lncRNA GAS5, triggering apoptosis in ECs 71 .…”
Section: Pathological Roles Of Mφ-evs In Diseasementioning
confidence: 99%
“…For example, EVs from atherogenic macrophages promote plaque formation in atherosclerosis. These EVs restrained the migration of naïve macrophage out of plaques and reduced the growth and tube formation of endothelial cells (ECs), increasing plague progression 69 , 70 . Moreover, excessive lipoproteins accumulation induces the release of Mφ-EVs enriched with lncRNA GAS5, triggering apoptosis in ECs 71 .…”
Section: Pathological Roles Of Mφ-evs In Diseasementioning
confidence: 99%
“…Likewise, exosomes derived from mature dendritic cells are involved in the progression of endothelial inflammation via vesicular tumor necrosis factor-α (TNF-α)-mediated NFκB pathways [ 135 ]. Oxidized low-density lipoprotein-stimulated macrophages suppress tube formation in endothelial cells via exosomes [ 136 ]. Together, these studies provide strong evidence that exosomes can modulate endothelial metabolism and functions.…”
Section: Exosome-mediated Remodeling Of Endothelial Gene Expressiomentioning
confidence: 99%
“…It has been established that atherosclerosis is characterized by ox-LDL induced inflammation, endothelial injury, apoptosis and phonotype changes of vascular cells and platelet activation. Most recent studies demonstrated that, the exosomal pathway for communication of macrophages and vascular endothelial cells modulates the apoptosis and inflammation response, participating in the pathophysiology of atherosclerosis [3, 14, 15, 16]. Furthermore, the communication between endothelial cells and smooth muscle cells mediated by exosomes affects the inflammation and phonotype changes of vascular cells, which are closely associated with the progression of arthrosclerosis [17].…”
Section: Exosomes-related Non-coding Rnas and Cvdsmentioning
confidence: 99%
“…Furthermore, the communication between endothelial cells and smooth muscle cells mediated by exosomes affects the inflammation and phonotype changes of vascular cells, which are closely associated with the progression of arthrosclerosis [17]. Huang C et al [15] revealed that, inhibiting the secretion of exosomes by ox-LDL-stimulated macrophages restored the growth and tube formation of endothelial cells. The findings of Chen L et al [16] revealed that exosomes derived from IncRNA GAS5 over-expressed THP-1 cells enhanced the apoptosis of vascular endothelia cells, suggesting that exosomes-associated IncRNA GAS5 regulated the apoptosis of macrophages and endothelial cells.…”
Section: Exosomes-related Non-coding Rnas and Cvdsmentioning
confidence: 99%